Chattering analysis of an electro-hydraulic backstepping velocity controller - Eny, Gérémino Ella; Eya, Honorine Angue Mintsa; Nzue, Rolland Michel Assoumou; Senouveau, Nzamba (Zielona Góra: Uniwersytet Zielonogórski)
This paper focuses on the chattering analysis in a backstepping controller used to drive an electro-hydraulic servo system. The chattering phenomenon, well known in sliding mode control, strongly reduces operating performance while causing premature wear of the system. Four cases are studied to highlight the factors influencing the chattering in the backstepping control.
Keywords: chattering analysis; backstepping controller; electro-hydraulic servo system; sensitivity analysis; fast unmodeled dynamics